Sociological investigation results of Ukraine municipal governance representatives about the implementation of the regional pathoanatomical center project promotion - Rosha, L. G. (Journal of Education, Health and Sport, 2018)
The aim is to evaluate the opinion among the municipal administration representatives (MAR) of Ukraine, about the prospects of the regional pathoanatomical center (RPC) project. Materials and methods. According to a specially designed questionnaire, 106 municipal officials were interviewed. Statistical processing of the obtained results is carried out using generally accepted statistical methods. Results. The estimation of the prospects of the implementation of the RPC project is given, the current trends of the municipal government are taking into account. Conclusions. The results of the study showed that in accordance with the views of the responded municipal officials, the modern system of PAS needs reform.